Ordering theories: Typologies and conceptual frameworks for sociotechnical change. (October 2017) - Sovacool, Benjamin K; Hess, David J
What theories or concepts are most useful at explaining socio technical change? How can – or cannot – these be integrated? To provide an answer, this study presents the results from 35 semi-structured research interviews with social science experts who also shared more than two hundred articles, reports and books on the topic of the acceptance, adoption, use, or diffusion of technology. This material led to the identification of 96 theories and conceptual approaches spanning 22 identified disciplines. The article begins by explaining its research terms and methods before honing in on a combination of fourteen theories deemed most relevant and useful by the material. These are: Sociotechnical Transitions, Social Practice Theory, Discourse Theory, Domestication Theory, Large Technical Systems, Social Construction of Technology, Sociotechnical Imaginaries, Actor-Network Theory, Social Justice Theory, Sociology of Expectations, Sustainable Development, Values Beliefs Norms Theory, Lifestyle Theory, and the Unified Theory of Acceptance and Use of Technology. It then positions these theories in terms of two distinct typologies. Theories can be placed into five general categories of being centered on agency, structure, meaning, relations or norms. They can also be classified based on their assumptions and goals rooted in functionalism, interpretivism, humanism or conflict. The article lays out tips for research methodology before concluding with insights about technology itself, analytical processes associated with technology, and the framing and communication of results. An interdisciplinary theoretical and conceptual inventory has much to offer students, analysts and scholars wanting to study technological change and society.